Design of starch-formate compound fibers as encapsulation platform for biotherapeutics. (20th February 2017) - Lancuški, Anica; Abu Ammar, Aiman; Avrahami, Ron; Vilensky, Rita; Vasilyev, Gleb; Zussman, Eyal
Graphical abstract: Starch-formate/glycerol compound fibers, processed into nonwoven mat using coaxial electrospinning technique. Neat core-sheath morphology of the fibers was obtained, successfully encapsulating lactobacillus paracasei strains as a model biotherapeutic product. Highlights: Starch fibers loaded with cells were successfully fabricated using coaxial electrospinning. Starch-formate/glycerol interactions with time. Spinnabillity of starch. Coaxially electrospun starch fibers offer a versatile encapsulation platform for of biotherapeutics. Encapsulated cells stability. Abstract: Effective encapsulation and protection of biotherapeutics using a bio-based carrier, preferably issued from renewable resources, remains a challenge. Herein, we demonstrate application of coaxial electrospinning to fabric starch-based core-sheath compound fibers as a bacterial cells' carrier. Starch-formate is employed as an encapsulation agent, while the fiber core is made of glycerol, serving as a cell suspension medium. SEM microscopy reveals a distinct core-sheath morphology of the starch-formate/glycerol (SFG) compound fibers with mean diameters of 4.13 ± 1.05 μm. Calorimetric and thermomechanical analyses and FTIR spectroscopy show a progressive interaction between the starch-formate and the glycerol with time, pronounced with temperature increase. SFG fibers with encapsulated Lactobacillus paracasei are proved stable with retained bacterial viability when stored at 4 °C and room temperature for up to 21 days. SFG fibers present a potential biotherapeutic products' encapsulation platform, guaranteeing the stability at refrigerated and ambient storage conditions, as determined in this study.